Ardisia kalimbahin (Primulaceae, Myrsinoideae), a new species from the Philippines - Magtoto, Liezel M.; Tamayo, Maverick N.; Udasco, Jr., Leonardo C.; Bustamante, Rene Alfred Anton (Phytotaxa, 2021)
Ardisia kalimbahin is herein described and illustrated as a new species. It is the latest addition to the richness of Ardisia in the Philippines. It closely resembles A. romanii Elmer but is distinct in having shorter petiole, shorter elliptic leaves, racemose inflorescence, longer and sparsely puberulent pedicels, magenta corolla lobes, basifixed anthers, shorter filaments, and a beaked stigma. Based on current collection and available herbarium specimens, Ardisia kalimbahin is distributed in the islands of Palawan (Aborlan), Mindoro, and Luzon (Carranglan). Available data is not enough to assess its conservation status; hence, it is proposed as data deficient (DD).